The surroundings and the age of the upper paleolithic site on Susak island - Schweitzer, Ferenc; Kis, Éva (Acta Geographica Debrecina Landscape & Environment series, 2016)
Our study investigates the paleoenvironmental conditions of an Upper Paleolithic site found in the excavation of the North Adriatic Susak Island. Our research explores the range of the loess and loesslike sediments deposited on rudist limestone which is the substratum of the island. We studied the Quaternary sediments by a coherent paleoenvironmental assessment method. The geomorphological and the various chronological analysis contribute significantly to the extension of our knowledge on the paleoenvironmental conditions of the Upper Paleolithic site (Radiocarbon age is 31,830 ±720 yr BP) on Susak Island.